Examining the effects of movement activities of coordinated approach to child health (Catch) program on locomotor and manipulative skills of 4-5 years old children - Kılıç, Zeynep; Uyanık, Gülden; Çağlak Sarı, Saime (Ozgen Korkmaz, 2022)
The main objective of the research is to examine the impact of regular implementation of Education Program made of CATCH Program Movement Activities on the locomotor and manipulative skills of preschool children. Implementation of Education Program made of CATCH Program Movement Activities was carried out in an independent preschool located in Kadıköy District in Anatolian Side of İstanbul Province, Turkey. Purposeful sampling method was used to determine the school where the experimental designed study will be conducted. The study group of the research consists of 64 children, 32 in experiment group and 32 in control group. To determine the efficiency of Education Program made of CATCH Program Movement Activities, education program was implemented with experiment groups for two days a week during 9 weeks. According to the results of pre-test and post-test measurements of experiment and control groups, no significant difference was determined between the locomotor subdimension, manipulative subdimension of the measurement instrument and measurement instrument total scores in pre-test measurements of the children (p>.05). According to the analysis results of post-test measurements following movement program, it was determined that there is a significant difference in locomotor subdimension, manipulative subdimension of the measurement instrument and measurement instrument total scores of both 4 and 5 years old children in favour of the experiment group (p<.05).
Keywords: Catch Movement Program; Locomotor Skills; Manipulative Skills